IDEOLOGICAL SYMULACRAAS A TOOL TO MOBILIZE CITIZENS IN UKRAINE - Власенко, Т.Т. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The article is devoted  tothe establishment and operationof simulacrain Ukrainian political discourse. The author analyzes the mechanism of usingideologicalsimulacraas a tool tomobilize citizens, in particular, considers the effect ofsimulacrareformattingpolitical realitiesin Ukraine.The author investigates theproduction ofsymbols andsimulacrain a crisisof political power.